Comparison of intraosseous and intravenous iodinated contrast administration for CT imaging in Hispaniolan Amazon parrots (Amazona ventralis). Issue 5 (16th May 2022) - Jania, Rachel; Tully, Thomas; Mitchell, Mark; Granger, L. Abbigail
Abstract: Establishing and maintaining intravenous access for contrast medium during CT imaging can be difficult in birds due to their small size and thin walled vessels. Intraosseous (IO) catheters are an alternative to intravenous catheters and are often used for fluid or medication administration in birds. To determine the feasibility of IO iodinated contrast enhancement for CT in birds, 10 adult Hispaniolan Amazon parrots ( Amazona ventralis ) weighing 260–325 g, were enrolled in a prospective randomized blinded crossover group study to evaluate the differences in contrast route administration. The parrots underwent pre‐ and postcontrast CT scans using both routes of contrast administration with a wash‐out period of at least 1 week between the two methods. Scans were evaluated subjectively for diagnostic quality and objectively with Hounsfield units measured over three organs: the brain, right kidney, and liver. All scans were diagnostic, and there was no statistically significant measurable difference in contrast enhancement between the two methods in any of the three organs. Subjectively, IO catheters were technically more difficult to place, but once in place, they were easier to manipulate for the imaging procedure and provided no complications upon removal. Minimal adverse side effects were noted from the IO catheters. In this small study, IO iodinated contrast administration was comparable in enhancement characteristics to intravenous administration for CT imaging in Hispaniolan Amazon parrots.